A silicon-oxide-silicon vertically separated electrode nanogap device structure - Noor, N. H. M.; Uda, Hashim, Prof. Dr.; Muhamad Emi Azry, Shohini; Nuri, A. M. M. (American Institute of Physics, 2010)
Link to publisher's homepage at http://proceedings.aip.org/